The skyscrapers of New York - Dobson, F. A. (American history in video., 1906)
This melodrama was filmed during the actual construction of a skyscraper in New York City, and includes several scenes of real work crews: a line of bricklayers, a man heating rivets in a forge, riveters assembling steel girders, men astride the steel framework maneuvering and setting a girder in place, and a group of men descending on a crane line. The story involves a construction foreman who fires one of his crew for fighting, which leads the disgruntled employee to steal. He causes the blame to be put on the foreman, who is finally exonerated when the thief is exposed. All of this conflict is woven in and around the actual construction of the building as the work is in progress. There is even one scene of a hand-to-hand fight between the foreman and the villain that takes place on the unprotected ledge of the steel framework of the building. Some New York City landmarks seen in the film include Union Square (between Broadway and 4th Avenue, 14th-17th Street), and the Everett House, opposite the northeast corner of the square at 17th St. and 4th Avenue. The film includes the original AM & B title frames at head of film.